A d10 Ni–(H2) Adduct as an Intermediate in HH Oxidative Addition across a NiB Bond1. Issue 4 (9th December 2013) - Harman, W. Hill; Lin, Tzu‐Pin; Peters, Jonas C.
Abstract Bifunctional EH activation offers a promising approach for the design of two‐electron‐reduction catalysts with late first‐row metals, such as Ni. To this end, we have been pursuing H2 activation reactions at late‐metal boratranes and herein describe a diphosphine–borane‐supported Ni—(H2) complex, [(PhDPBiPr)Ni(H2)], which has been characterized in solution. 1H NMR spectroscopy confirms the presence of an intact H2 ligand. A range of data, including electronic‐structure calculations, suggests a d10 configuration for [(PhDPBiPr)Ni(H2)] as most appropriate. Such a configuration is highly unusual among transition‐metal H2 adducts. The nonclassical H2 adduct is an intermediate in the complete activation of H2 across the NiB interaction. Reaction‐coordinate analysis suggests synergistic activation of the H2 ligand by both the Ni and B centers of the nickel boratrane subunit, thus highlighting an important role of the borane ligand both in stabilizing the d10 Ni—(H2) interaction and in the H—H cleavage step.